Social Welfare Effects of Water Security Improvements in Arid Regions: The Case of Mendoza, Argentina - Farreras González, Verónica Inés; Lauro, Carolina; Abraham, Laura; Salvador, Pablo Federico (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2026)
Water security is a critical challenge in Mendoza, Argentina, an arid region that faces rising water demand and uncertainty caused by climate change. Agriculture consumes 90% of the fresh water in the region, while vineyards occupy just over 60% of the cultivated area. This study estimates the social welfare effects of an improvement in water security achieved by reallocating water from vineyards to other uses. We used a multidisciplinary approach, applying benefit transfer to estimate social welfare changes and water footprint to quantify shifts in water availability. Our findings suggest that a water security policy in the Mendocinian Northern Oasis can result in an average 21-percentage-point increase in annual water availability for other uses. This equals an average household welfare gain of 17.43 US dollars per year (95% CI: 8.40-35.64) at 2024 prices over the next 30 years. This study offers a framework for regions worldwide facing similar challenges of water scarcity, increasing water demand, and climate change. Moreover, it can support the design of more informed water management strategies to ensure long-term water security. Highlights: A framework is proposed for evaluating water security improvements in arid regions. Aligning water distribution with crop water needs enables efficient water allocation. Water security improvement policies increase social welfare for Mendocinian citizens. A multidisciplinary approach is developed using benefit transfer and water footprint. Water security improvement equals an annual welfare gain of 17.43 US dollars per household.